THE WATER SAVING, INCREASING WATER USE EFFICIENCY AND WATER PRODUCTIVITY OF MELON BY WATER RETENTION TECHNIQUE - HOMMADI, ALI HASSAN; MAJEED, GHAITH MOHAMMED ALI; HUSSIEN, HATEM HAMED (Journal of Duhok University, 2023)
The causes of water scarcity in Iraq is result of climate changes and the lack of water from the source, therefore, it necessitated searching for modern methods to conserve water and reduce its consumption and rationing. A modern technology in agriculture by set up polyathelines sheet under the root zones of plant was adopted for conserving thewaterirrigation into plantroot zones, to reduce waterlosses of field, increase the water usage efficiency and econimecals water productivities. The our search, the sheets was set up below rootzones of melon crop at the summer planting season 2022 by using the freefield. The studies were conducted in a farm pace in Babylon province inSadat-Al Hindyai Town. The drip-irrigation system was usage in wateringsystem. Two treatments were used, in plot A plastic sheet is used and plot B without sheet. The supplied irrigation and irrigation time are estimated, the yield, the water utilizeing Efficiency and water-productivity of crop which comparing with the 2 treatments. The plot A is increased 3.92% from plot B. In coliclosion show that water-utilizeefficiency for the plot A is higher than plot B by 22.62%. The water productivity is increasing of plot A comparing with plot B by 20.65%. The water saving in plot A was 19.6% comparing with plot B. The reducing in number of plants watering at plotA gave 11% comparing with plot B. The aim of the research is to obtain on the best ways to reduce water application of filed and reduction the losses of water by deep percolation and evaporation. This technology is helping in reducing irrigation water requirements also increasing productivity.